2010
DOI: 10.1111/j.1475-4754.2010.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Material Characterization of Ceramic Tile Mosaic From Two 17th-Century Islamic Monuments in Northern India

Abstract: Coloured tiles from two northern Indian monuments were analysed for their body and glaze composition. The results suggest that three different groups of tiles were used, all comprising a stonepaste body with alkali glaze. One group has strong similarities to a major Indian glass group, known as high alumina mineral natron glass, while the other two are similar to Western and Central Asian plant ash glazes, although with much lower lime content. The colorants conform with those usually employed in pre‐modern gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The EPMA measurements indicated that manganese (1.2%: Table 1) was used to colour the purple alkaline glazes. This is consistent with the historic use of manganese for purplish hues in glazes [3,12,27,30]. In addition, few crystals of iron oxide were also observed in the glaze matrix.…”
Section: Purple Glazesupporting
confidence: 87%
See 2 more Smart Citations
“…The EPMA measurements indicated that manganese (1.2%: Table 1) was used to colour the purple alkaline glazes. This is consistent with the historic use of manganese for purplish hues in glazes [3,12,27,30]. In addition, few crystals of iron oxide were also observed in the glaze matrix.…”
Section: Purple Glazesupporting
confidence: 87%
“…The presence of lead, tin and zinc in the same ratio as for the S32Y and S82Y yellow glazes (Table 1) suggests that green glazes were made in part from yellow glazes [27]. Regarding the blue colouring agents, the Cu/Co ratio of the green glaze sample differed from the ratios in the S52B and S76B blue glazes.…”
Section: Green Glazementioning
confidence: 84%
See 1 more Smart Citation
“…In this sense, limestone for the white tesserae and tephritic lava for the black tesserae were identified [11]. On the other hand, other research works [24][25][26] used portable non-invasive techniques in order to characterize in situ the materials used in the decoration objects. Concretely in these latter works [24][25][26] some tesserae from a mosaic located in the Domus of Octavius Quartio (Pompeii) were analyzed with portable instrumentation obtaining interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of two varieties of lead–tin yellow type II particles in yellow and green glazes, one with associated silica content and the other significantly with an associated zinc content was first established by the authors (Gill and Rehren ) on the analyses of 17th‐century glazed tiles from two sites in northern India. This was later corroborated by similar findings reported on the analyses of yellow glazes from tiles on contemporaneous monuments in Lahore, Pakistan (Gulzar et al .…”
Section: Introductionmentioning
confidence: 99%